Preface - Burnell, Joel (Jonathan Edwards studies, 2014)
This special issue, Volume 4, No. 2 (2014) of the Jonathan Edwards Studies Online Journal, include papers that were among those presented in June 2011 at the International Jonathan Edwards Conference, held in Wroclaw, Poland at the Evangelical School of Theology (EST). The Conference, organized by the Jonathan Edwards Center Poland gathered scholars from four continents and eight countries, representing 15 universities and 6 international Jonathan Edwards Centers.